Evaluating the Shift from Television Advertising to Influencer Marketing in Public Relations Industry in Nigeria - Olaoluwakitan, Akande, Oluwanifemi; Akin-Odukoya, Omolara Oluwabusayo (Budapest International Research and Critics University, 2025)
The advertising and marketing sector keeps evolving with technology and this transformation poses a threat to traditional media platforms. Therefore, this study evaluates the shift from television advertising to influencer marketing in the Nigerian Public Relations Industry. This research is supported by the Media Ecology Theory. Media Ecology Theory explores how different forms of media shape communication and societal interactions, explaining how social media-driven influencer marketing is altering traditional advertising dynamics. Media Consumption Theory examines how audiences interact with media content, providing an inside look into the transition from television to digital platforms. A sample of 100 public relations professionals were administered questionnaires. The data collected were on the factors of shifting to influencer marketing, the effectiveness of influencer marketing strategy, prospects of influencer marketing, how the techniques of influencer marketing were influenced by digital interactions and social media platforms, and the long-term effects of this shift. The data obtained through questionnaires were analyzed using the Statistical Package for Social Sciences (SPSS) version 29 to assess the factors of influencer marketing compared to television advertising and also, the perceived effectiveness of influencer marketing. The result indicates reaching a wider audience (30%), better targeting of niche demographics (28%), and more audience engagement (38%), are the factors driving the transition. The influencer marketing strategies with high positive deviations above the mean are brand visibility (3.38), and audience engagement (3.40). Conclusively, the benefits attached to influencer marketing are the factors that influence the shift. It is therefore recommended that the potential of influencer marketing be maximized to the fullest.